2011
DOI: 10.1177/1545968310389183
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Integrity Is a Stronger Predictor of Motor Function Than BOLD Response in Patients With Stroke

Abstract: Objective Neuroimaging techniques, such as diffusion tensor imaging (DTI) and blood oxygenation level–dependent (BOLD) functional magnetic resonance imaging (fMRI), provide insights into the functional reorganization of the cortical motor system after stroke. This study explores the relationship between upper extremity motor function, white matter integrity, and BOLD response of cortical motor areas. Methods Seventeen patients met study inclusion criteria; of these 12 completed DTI assessment of white matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 40 publications
5
75
3
Order By: Relevance
“…This finding is consistent with prior studies that reported a negative relationship between the TMS-induced modulation of visual sensitivity and the fronto-tectal WM connectivity (Quentin et al, 2013(Quentin et al, , 2014. Considering the 'virtual-lesion' model, in which inhibitory rTMS might act as a breakdown of the function associated to the targeted area, these results are also in line with previous clinical studies in traumatic brain injury (TBI) (Strangman et al, 2012) and stroke patients (Qiu et al, 2011). In these studies, FA predicts their prognosis, that is to say, FA is considered as a biomarker that might anticipate which of these patients will recover their functional deficit and which not.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with prior studies that reported a negative relationship between the TMS-induced modulation of visual sensitivity and the fronto-tectal WM connectivity (Quentin et al, 2013(Quentin et al, , 2014. Considering the 'virtual-lesion' model, in which inhibitory rTMS might act as a breakdown of the function associated to the targeted area, these results are also in line with previous clinical studies in traumatic brain injury (TBI) (Strangman et al, 2012) and stroke patients (Qiu et al, 2011). In these studies, FA predicts their prognosis, that is to say, FA is considered as a biomarker that might anticipate which of these patients will recover their functional deficit and which not.…”
Section: Discussionsupporting
confidence: 92%
“…Our lesion maps are consistent with this localization. More generally, our study is consistent with the results of studies that show that UL motor function after stroke correlates better with axonal integrity in the posterior limb of the internal capsule (as determined by diffusion tensor imaging) than it does with engagement of the ahPCG, as determined by blood oxygen-level dependent fMRI [26].…”
Section: Discussionsupporting
confidence: 91%
“…[5][6][7][8][9] Tractography in those chronic cases indeed demonstrates a reduction of the tract volume, which may be interpreted as atrophy secondary to anterograde degeneration. 10,11 These metrics of PT integrity also seem to better correlate with motor impairment than lesion size alone 12 or task-based fMRI motor network activity 13 but are highly correlated with functional resting-state connectivity.…”
Section: Pyramidal Tract Integrity In Chronic Strokementioning
confidence: 95%